The in vitro effects of HAART on the expression of muci and NFkB1 in a cervical cancer cell line, HCS-2 - Thabethe, Kutlwano Rekgopetswe (My University, 2015)
Cervical cancer is the third most commonly diagnosed cancer globally and it has also been identified as one of three AIDS defining malignancies. Highly active antiretroviral therapy (HAART) is a combination of three or more antiretroviral drugs which are classified as nucleoside/nucleotide reverse transcriptase inhibitors (NRTIs), non-nucleoside reverse transcriptase inhibitors (NNRTIs) and protease inhibitors (PIs). HAART has been shown to play a significant role in reducing the incidence of some AIDS defining malignancies, although its effect on cervical cancer is still unclear. It is hypothesized that HAART might reduce cancer risk by interacting with different signalling molecules and pathways that are involved in cancer in order to induce cell death and thus inhibit cell proliferation. The broader aim of this study was to understand the relationship between cervical cancer and HAART. This was achieved by studying the expression of key signalling molecules in cancer; MUC1 and NFkB (P65) and morphological features using scanning electron microscopy following 24 hour treatment of a cervical cancer cell line, HCS-2 with drugs which are commonly used as part of HAART; Emtricitabine (FTC), Tenofovir disoproxil fumarate (TDF), Efavirenz (EFV), Atripla combination (ATP) and Kaletra combination (LPV/r) at their clinical plasma concentrations. Quantitative real time polymerase chain reaction (qPCR) was used in order to study the gene expression of MUC1 and P65 and the data was analysed using the 2-ΔΔCT method to calculate fold change. The statistical analysis was conducted using JMP 11 software. MUC1 and P65 gene expression was reduced following drug treatment. Protein expression was studied by means of Immunofluorescence and MUC1 and P65 protein expression was reduced following drug treatment. Scanning electron microscopy revealed characteristic features of apoptotic cell death such as loss of cell contacts, reduced density and size of microvilli, increase in surface blebbing and budding and degradation of apoptotic bodies following treatment with all the drugs. In conclusion, the drugs used in this study
Keywords: Uterine Cervical Neoplasms; Antiretroviral Therapy, Highly Active